2020
DOI: 10.1007/s42729-020-00217-x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Phosphate Rock to Improve Nutrient Uptake, Phosphorus Use Efficiency, and Carrot Yields

Abstract: The objectives of this study were to assess (a) the efficiency of lemon and pineapple juices and the concentration and time needed to release more than 50% of available phosphorus from phosphate rock (PR), and (b) the effect of different types of PR management on carrot yields, nutrient uptake, and phosphorus use efficiency. Field trials were set up at two sites with humic andosols and orthic acrisols over two seasons in Kenya. In a randomized complete block design, replicated three times, the following treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…El biol combinado con la enmienda solida muestra ser más eficaz en solubilizar la roca fosfórica para liberar P disponible, presumiblemente al contenido de ácidos orgánicos en el biol y a un mejoramiento en las condiciones del pH del suelo. Sobre esta respuesta Mwangi et al, (2020) explicaron que el 44 % de la solubilización de rocas fue causado por el pH y presencia de ácidos orgánicos, además el biol contiene un 50% de N en formas amoniacales y un 60% de P en forma inorgánica que despueś de su aplicación al suelo es rápidamente asimilado por la planta. Esta mayor transferencia de macro y micronutrientes por el biol en comparación con abonos a base de rocas fue explicada por Lourenzi et al, (2021), además de su contribución a mejorar las cosechas (Bacca et al, 2020).…”
Section: Discussionunclassified
“…El biol combinado con la enmienda solida muestra ser más eficaz en solubilizar la roca fosfórica para liberar P disponible, presumiblemente al contenido de ácidos orgánicos en el biol y a un mejoramiento en las condiciones del pH del suelo. Sobre esta respuesta Mwangi et al, (2020) explicaron que el 44 % de la solubilización de rocas fue causado por el pH y presencia de ácidos orgánicos, además el biol contiene un 50% de N en formas amoniacales y un 60% de P en forma inorgánica que despueś de su aplicación al suelo es rápidamente asimilado por la planta. Esta mayor transferencia de macro y micronutrientes por el biol en comparación con abonos a base de rocas fue explicada por Lourenzi et al, (2021), además de su contribución a mejorar las cosechas (Bacca et al, 2020).…”
Section: Discussionunclassified
“…Non-microbial techniques include use of acidifying agents such as lemon and pineapple juices (Mwangi et al, 2020) or buttermilk (Cicek et al, 2020). These approaches are, however, only feasible on small-scale field applications.…”
Section: Introductionmentioning
confidence: 99%
“…The use of rocks to obtain nutritional gains can be done in different ways. For example, Mwangi et al (2020) concluded that the dissolution of phosphate rock with lemon juice and its combined application (immediately after dissolution) with compost at planting improves nutrient uptake, phosphorus use efficiency and crop yields of Daucus carota L. On the other hand, Boroumand et al (2020), working with Nasturtium Research, Society andDevelopment, v. 9, n. 12, e5591210790, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.10790 officinale R. Br. and phosphate solubilizing bacteria from rhizospheres, enhanced the soil nitrogen and phosphorus content and the vegetative growth of land cress plants.…”
Section: Introductionmentioning
confidence: 99%